FRI0036 Meta-Immunological Profiling of Patients with Behçet's Disease Reveals Novel Biomarkers of Disease Activity, Progression and Response To Therapy. (15th July 2016) - Pucino, V.; Vitale, A.; Lucherini, O.M.; Talarico, R.; Marone, G.; Galeazzi, M.; Matarese, G.; Cantarini, L.
Abstract : Background: Behçet's disease (BD) is a rare and poorly understood condition characterised by systemic inflammation. Current biomarkers are still largely insensitive and unable to predict disease progression and response to treatment in BD patients. Objectives: The specific aims of this study were i) to explore serum levels of soluble CD40L (sCD40L), soluble intracellular-adhesion-molecule (sICAM-1), monocyte-chemoattractant-protein-1 (MCP-1), myeloperoxidase (MPO), leptin, resistin, osteoprotegerin (OPG), soluble-type 1 tumour-necrosis-factor-receptor (sTNFR), interleukin-6 (IL-6) and serum-amyloid-A (SAA); ii) to evaluate potential correlations between the putative circulating biomarkers with the demographic profile, disease activity, organ involvement, genetical background, and different therapeutic regimes. Methods: 57 serum samples were collected from 27 BD patients and 35 healthy controls (HC) after written consent. Demographic and clinical data are summarized in Table 1 . Adipocytokines were analyzed using the bead-based-analyte-detection-system. Data were acquired by flow-cytometry. SAA serum concentration was determined with a enzyme linked-immunosorbent assay (ELISA). We used ANOVA test to identify statistical differences. P<0.05 was considered statistically significant. Results: BD patients showed higher levels of circulating sTNFR (p=0.008), leptin (p=0.0011), sCD40L (<0.0001), and IL-6 (p=0.0154) than HC while no difference was found in MCP-1, MPO, sICAM, and resistin serum levels. Patients HLA-B51- had higher sTNFR and sICAM-1 serum levels than HC (p=0.0034, p=0.0037, respectively), while sICAM levels were significantly higher in patients HLA-B51- than in patients HLAB51+ (p=0.0010) as well as leptin was significantly higher in both HLA-B51+ and HLA-B51- BD patients than in HC (p=0.0183, p=0.0303, respectively). Patients treated with biologic-agents showed significantly higher sTNFR and leptin serum levels when compared to DMARDs-treated-patients (p=0.0246, p=0.0023, respectively). Moreover, sTNFR was found higher in patients with inactive disease and in patients over 40 years than HC (p=0.0104, p=0.0329, respectively). Conclusions: The identification of a specific meta-immunological profile associated with disease status and response to therapy may contribute to our understanding of the physiopathology processes underlying BD activity and damage as well as to provide useful tools for prognostic purposes and a personalized treatment approach. Disclosure of Interest: None declared